Annual and Seasonal Trends in Mastitis Pathogens Isolated from Milk Samples from Dairy Cows of California’s San Joaquin Valley Dairies Between January 2009 and December 2023 - Daniela R. Bruno; Karen H. Tonooka; Terry W. Lehenbauer; Sharif S. Aly; Wagdy R. ElAshmawy (Veterinary Sciences)
Bovine mastitis is a significant disease affecting dairy cattle worldwide, impacting milk quality and farm profitability. Understanding pathogen distribution is crucial for effective disease management. This study analyzed 319,634 individual cow milk samples submitted to the UC Davis Milk Quality Laboratory between 2009 and 2023 to assess pathogen prevalence, seasonal variations, and long-term trends. Routine microbiological cultures identified major and minor mastitis pathogens, with additional testing for Mycoplasma spp. Statistical analyses evaluated annual and seasonal trends in bacterial isolation rates. Results indicated that environmental pathogens, particularly non-aureus staphylococci and coliforms, were most frequently isolated, while contagious pathogens (Staphylococcus aureus, Streptococcus agalactiae, and Mycoplasma spp.) were less prevalent. Seasonal trends revealed higher contamination rates in Winter and increased no-growth samples in Summer. The study also observed a decline in sample submissions in recent years, possibly reflecting evolving dairy management practices. These findings provide a comprehensive perspective on mastitis pathogen dynamics in California’s Central Valley, supporting improved milk quality control measures and tailored mastitis prevention strategies.